UNSOLVABILITY OF TYPE CORRECTNESS PROBLEM FOR FUNCTIONAL PROGRAMS - Arakelyan, A.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In the present paper the type correctness problem is considered for functional programs without the type information. The aim of this research is to prove that there is no algorithm to reject all programs, during execution of which the type error would occur and accept all programs, during execution of which the type error would not occur.
Keywords: term; redex; reduction strategy; type error